Tinjauan Strategis Perencanaan Infrastruktur Transportasi Berkelanjutan dan Berwawasan Lingkungan di Kawasan Ibu Kota Negara (IKN) Nusantara - Hapriyanto, Aditya Restu; Azmi, Hafidzul (Universitas Batanghari Jambi, 2024)
The development of sustainable transportation infrastructure in the Ibu Kota Ngara (IKN) Nusantara is an important issue in the context of the capital's relocation to East Kalimantan, Indonesia. Related research highlights key challenges such as environmental impacts, socio-economic changes, and the integration of technology in transportation that come into focus in planning and implementing sustainable infrastructure. Two of the analyzed studies emphasize the importance of setting and applying sustainable development principles as a foundation for this project. Efforts to develop smart transportation hubs based on digital technology are also highlighted to support sustainability. Through innovative solutions such as the application of electric energy in transportation and strategic policy development, transportation infrastructure that is efficient, environmentally friendly, and suits the needs of the people in IKN Nusantara can be realized. In conclusion, an integrated approach between policy, technology, and understanding of environmental impacts is key to achieving sustainable transportation infrastructure in the region.